Research on Entrepreneurial Ability Model of College Students in Big Data Era—— A Case Study of “San Xun Flower Shop” - Sun, Heming; Wang, Caiying (Journal of Social Science Studies, 2022)
Innovation and entrepreneurship education is a new requirement for education under the situation of rapid social development in the new era. It is an important quality education in the current education system, and its essence is a skill education. Since the concept of "mass innovation, national entrepreneurship" was put forward, the innovation and entrepreneurship education for college students has been carried out in China, and some results have been achieved. But from the overall point of view, the innovation and entrepreneurship education of college students in China should be improved, and a specific, complete and scientific education system has not yet been formed. On this basis, this article analyzes the current problems in the education of cultivating college students’ innovation and entrepreneurship ability according to the experience of the project of “San Xuan Flower Shop”, and proposes some suggestions for reference.